Exploration of new 3α-pregnenolone ester analogues via Mitsunobu reaction, their anti-HIV activity and molecular modeling study - Mahdi, Kuthair Mohammed; Abdul-Reda, Nabeel Abed; Al-Masoudi, Najim Aboud (European Journal of Chemistry, 2015)
A new series of (5-pregnen-20-on-3α-yl)-substituted-benzoate analogues (10-13), (5-pregnene-20-on-3α-yl)-3-(substituted)acrylate derivatives (17-19) as well as the (17-(2-acetoxyacetyl)pregen-3α-yl)-3,4,5-trihydroxybenzoate (21) were synthesized from the β-pregenenolone scaffolds, by applying Mitsunobu reaction. All new compounds were characterized by 1H, 13C and 2D NMR spectroscopy. The inversion in configuration at C-3 during the formation of α-ester analogues was confirmed by NOESY NMR spectroscopy. The new compounds were evaluated for their in vitro antiviral activity against the replication of HIV-1 and HIV-2 in MT-4 cells. Compounds 18 showed an EC50 value of >1.95 mg/mL. In addition, preliminary structure-activity relationship and molecular modeling of compound 18 has been studied.